Pentingnya Pendidikan Bahasa Dalam Membangun Karakter Yang Berbudaya Di SMP PGRI 9 Sidoarjo - Tri Diantami; Siwi Widura Yuwana; Eni Nurhayati (Pusat riset dan Inovasi Nasional, 2023)
This article aims to discuss in detail the importance of language education in building a cultured character at the PGRI 9 SIDOARJO Junior High School level. Language education has a very important role in shaping the character of students, especially during adolescence which is a crucial period in the formation of their personality. Language education at Junior High School PGRI 9 SIDOARJO provides opportunities for students to develop language skills, both in speaking, writing, reading and listening. Students learn grammar, vocabulary, and language skills needed in everyday life. Language education is also important in building a cultured character. Students are exposed to literary works that represent diverse cultural values, develop empathy, tolerance and understanding of cultural diversity. Language education teaches good communication ethics, respect for the opinions of others, courtesy, and honesty. Students learn to respect and understand the perspectives of others and communicate effectively by taking into account social and cultural contexts. Good language skills open doors for students to acquire new knowledge and access broader information. Language education provides a strong foundation for students in studying other subjects, developing interests and talents, and facing challenges in an increasingly global world of work. This article emphasizes the importance of language education in building cultured character at Junior High School PGRI 9 SIDOARJO. Language education improves language skills, understands culture, and develops inclusive, empathetic, and communicative characters